2013
DOI: 10.1093/bja/aet020
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed therapy in cardiac surgery: a systematic review and meta-analysis

Abstract: The use of pre-emptive GDT in cardiac surgery reduces morbidity and hospital length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(156 citation statements)
references
References 35 publications
4
141
0
11
Order By: Relevance
“…In accord with the mean duration of hTEE probe insertion [17], our results emphasize the role of cardiac visualization early in the postoperative course in order to detect (new) cardiac dysfunction, i.e. especially RV failure, optimize hemodynamics and improve patients management [11,16]. In this context, it is worth noticing that we observed a non-significant trend towards improved in-hospital mortality in the hTEE group.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accord with the mean duration of hTEE probe insertion [17], our results emphasize the role of cardiac visualization early in the postoperative course in order to detect (new) cardiac dysfunction, i.e. especially RV failure, optimize hemodynamics and improve patients management [11,16]. In this context, it is worth noticing that we observed a non-significant trend towards improved in-hospital mortality in the hTEE group.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, in cases of unexplained life-threatening hemodynamic instability-possibly persisting despite corrective therapy-a multiplane transesophageal echocardiographic examination is recommended (Class I indication) to identify the underlying pathophysiological cause, e.g. hypovolemia, reduced myocardial contractility, pericardial tamponade [9], and to guide goal-directed therapy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Проте при всіх цих зазначених перевагах не спостерігається зменшення летальності. Аналогічні результати ра-ніш було отримані H. Aya [61,62].…”
Section: рідинне забезпечення у хворих із супутньою патологією серцевunclassified
“…On the other hand, in cardiac surgical patients only another four RCT focused on GDT were published: two of these studies used PAC [99,100] and two used esophageal Doppler monitoring [101,102] in the study arm. None of these seven GDT-RCT (all were single-centered, less than 1,000 patients studied in all studies between 1995 and 2012) demonstrated their usefulness in decreasing mortality in cardiac surgical patients, but they did reduce morbidity (postoperative complications) and hospital length of stay [5,103,104]. There are some potential causes which could explain the fact that despite the application of modern flow-related GDT protocols the results in cardiac surgery are poor related to mortality and in contrast with the data found in non-cardiac surgery.…”
Section: The Place Of Apw Monitoring Devices In Gdt In Cardiac Surgicmentioning
confidence: 99%
“…The last decade was characterized by a growing interest in innovating, less invasive devices that could be substituted for the PAC. Some of these new techniques were integrated into appropriate protocols that guide the hemodynamic evaluation and the subsequent therapeutic interventions and it was proven that their optimal use can reduce the morbidity, the mortality and can improve the outcome in both surgical [5][6] and non-surgical patients [7]. These recent technologies DOI: http://dx.doi.org/10.21454/rjaic.7518.231.wvf…”
Section: Introductionmentioning
confidence: 99%